PENETAPAN KADAR FENOL TOTAL EKSTRAK ETANOL RIMPANG TEMU PUTIH (Curcuma zedoaria (Christm.) Roscoe) DENGAN PERBEDAAN KONSENTRASI PELARUT - Maulida, Mielsya; Nurhasnawati, Henny; Sundu, Reksi (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2025)
White Temu (Curcuma zedoaria (Berg.) Roscoe) has an actoxidant activity because it contains phenolic compounds. Phenolic compounds are aromatic compounds with a structure derived from benzene so that they have aromatic rings and the presence of one or more hydroxyl (OH) groups. This study aims to determine the total phenol content of white rhizome ethanol extract with the difference in solvent concentration using UV-Vis spectrophotometry. The research conducted is an experimental research. The results showed that the rhizome of white temu contained secondary metabolite compounds in the form of phenolics, alkaloids, flavonoids, saponins, and terpenoids. Based on the results of determining the total phenol content of white temu extract with a difference in ethanol solvent concentrations of 30%, 50%, and 70%, the levels were 23.4477±0.9827 mg GAE/g, 32.2464±1.3022 mg GAE/g, and 51.6880±0.4948 mg GAE/g. The results of statistical analysis obtained normal and homogeneous data so that a one-way anova test with p value results was used(0.00) < (0.05) so it can be concluded that there is a significant difference in the total phenol levels of the three samples.